Pencatutan Kartu Tanda Penduduk Tanpa Persetujuan yang Dilakukan Oleh Calon Kepala Daerah Sebagai Tindak Pidana Pemilu - Rahma, Balgis Faradillah Aulia; H, Hufron (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The unauthorized use of Electronic Identity Cards (KTP-el) by regional head candidates is a serious issue that threatens the integrity of elections in Indonesia. This practice involves the use of citizens' personal data without consent to meet the support requirements for independent candidates in regional head elections (pilkada). According to Article 185A paragraph (1) of Law No. 10/2016, this act is classified as a criminal offense with a minimum imprisonment of 36 months and a maximum of 72 months, and a fine of at least IDR 36 million and a maximum of IDR 72 million. If the violation is committed by election organizers, the penalty is increased by one-third of the maximum penalty. Additionally, the unauthorized use of KTP-el also violates the Personal Data Protection Law (UU PDP), which mandates that personal data controllers must protect personal data during processing. Violations can result in criminal penalties of up to 5 years imprisonment and/or fines of up to IDR 5 billion, as well as administrative sanctions such as written warnings, temporary suspension of all data processing activities, deletion or destruction of personal data, and administrative fines. This study highlights the importance of strict law enforcement against unauthorized use of KTP-el to maintain public trust in the democratic process. Furthermore, education and socialization are needed to inform the public about their rights regarding personal data and the importance of reporting violations. Thus, it is hoped that elections can be more transparent, fair, and democratic.